Antibacterial properties of organic germanium against some human pathogens - SUDHA SELLAPPA; VINODHINI JEYARAMAN (International Journal of Pharma and Bio Sciences, 2011)
The antibacterial activity of Ge-132 (bis-betacarboxy-ethylgermanium sesquioxide/organic germanium) was investigated against gram positive (Bacillus subtilis, Streptococcus pyogenes and Methicillin-resistant Staphylococcus aureus) and gram negative bacteria (Aeromonas veronii, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Vibrio fischeri) using well diffusion and broth micro dilution technique test. Ge-132 showed inhibition activity towards both gram positive and gram negative bacterial species except E. coli. The results demonstrate that the test compound showed greater high inhibitory activity against gram positive strains than gram negative strains. Treatment for 250µg/ml concentration within 8-12h incubation results a maximum inhibition. Our findings suggest that organic germanium compound have potential to be developed as an antimicrobial agent against some bacterial infections.